2010
DOI: 10.1007/s00125-009-1651-x
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic status influences the nature and severity of coronary artery disease

Abstract: Aims/hypothesis We sought to understand the relationships between glycaemic status and both severity and progression of coronary artery disease (CAD), the leading cause of death in diabetes. Methods Baseline fasting blood glucose (FBG) and HbA 1c (%) were measured in 426 patients with known or suspected stable CAD, who underwent coronary artery intravascular ultrasound (IVUS) at baseline and after a mean follow-up period of 664 days (range 257 to 961). The patients were categorised as normoglycaemic (n=226, 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 25 publications
6
21
0
Order By: Relevance
“…Patients with higher HbA1c may have lower compliance with diabetic as well as other cardiac medications and nonpharmacological interventions including lifestyle modifications accounting for higher risk of mortality. Furthermore, there is evidence that atherosclerosis can be more aggressive with higher HbA1c as evidenced in a study by Berry et al, 3 showing correlation between HbA1c and maximum percentage atheroma area at baseline and with change in plaque area using intravascular ultrasound. In several large clinical trials, tighter glycemic control has failed to show an improvement in macrovascular complications and death.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Patients with higher HbA1c may have lower compliance with diabetic as well as other cardiac medications and nonpharmacological interventions including lifestyle modifications accounting for higher risk of mortality. Furthermore, there is evidence that atherosclerosis can be more aggressive with higher HbA1c as evidenced in a study by Berry et al, 3 showing correlation between HbA1c and maximum percentage atheroma area at baseline and with change in plaque area using intravascular ultrasound. In several large clinical trials, tighter glycemic control has failed to show an improvement in macrovascular complications and death.…”
Section: Discussionmentioning
confidence: 96%
“…3 Elevated HbA1c levels in nondiabetic patients presenting with ST-segment-elevation myocardial infarction (STEMI) have been associated with adverse outcomes, 4 and an increase in HbA1c after PCI among nondiabetics has been associated with an increase in restenosis rate. 5 Although acute preprocedural hyperglycemia has been associated with worse outcomes in those undergoing PCI, 6 the association of HbA1c and outcomes after PCI is unclear.…”
Section: Iabetes Mellitus Adversely Affects Cardiovascular Outcomesmentioning
confidence: 99%
“…A low fasting blood glucose level and the use of ARBs have been reported to be negatively associated with the severity and progression of atherosclerosis in the coronary 13,14) and carotid arteries 15,16) . In the present study, asymptomatic ICAS represented less severe stenosis and an earlier stage of atherosclerosis than symptomatic ICAS.…”
Section: Independent Predictors Of Symptomatic and Asymptomatic Icasmentioning
confidence: 99%
“…Changes over time on IVUS also have been shown to correlate significantly, albeit weakly, with QCA measurements in another study. 57 Although IVUS has shown that patients with greater severity of recognized risk factors have more severe coronary atheroma, 58,59 the demonstration that atherosclerotic changes correlate with clinical outcomes would clearly constitute a major element favoring the use of this imaging modality in drug development. The Canadian Atherosclerosis Imaging Network (CAIN), funded by the Canadian Institutes of Health Research and Canada Foundation for Innovation, is presently conducting a large clinical study of patients undergoing serial coronary angiograms, coronary IVUS, and carotid ultrasound examinations for up to 2 years and in whom clinical events are collected for 5 years (www.canadianimagingnetwork.…”
Section: Ivusmentioning
confidence: 99%